KERJASAMA KEAMANAN "MALACCA STRAIT PATROL" ANTARA INDONESIA, MALAYSIA, SINGAPURA, DAN THAILAND TERHADAP TINGKAT KASUS PEMBAJAKAN DI SELAT MALAKA TAHUN 2016-2018 - Muhammad Salim Nadjieb (2021)
Piracy and Piracy have long been occurring in the Malacca Strait waters. The issueof piracy in the Malacca Strait area is an issue that could threaten the interests of countries that have interests in the waters of the Straits of Malacca, such as Indonesia, Singapore, Malaysia and Thailand in a cooperation forum, namely the Malacca Strait Patrol. The issue of piracy does not only involve Indonesia, Singapore, Malaysia and Thailand but there are other actors who have interests in the waters of the Malacca Strait. What makes this research interesting are the efforts made by the Malacca Strait Patrol which aim to reduce piracy cases in the Malacca Strait Area and protect the national interests of the countries involved in the Malacca Strait Patrol. The purpose of this research is for the reader to get a description of how and how current this security cooperation is and to know some of the dynamics of the cooperation between Indonesia, Singapore, Malaysia and Thailand in the Malacca Strait from 2016 to 2018. The research method used by the author in This research is a qualitative research with data collection methods using secondary data or literature study and this research is supported by the theory of International Security, the theory of Security Cooperation, and the concept of Maritime Security. From this study, the authors found that the Malacca Strait Patrol in the period from 2016 to 2018 had inconsistencies in efforts to create security stability in the Malacca Strait.